Being and practicing as a tutor at University - Inmaculada Lopez Martin; Purificación González Villanueva; Paloma Julia Velasco Quintana (Universitat Politècnica de València, 2013)
This study is part of the PhD thesis entitled "Meanings of university tutoring from the teachers' perspective", completed in 2012. The purpose was to understand the sense of tutoring at university through the teachers' perceptions. For it, we tried to know this scenario in order to understand its influence on the tutoring. Finally, we tried to understand further the teacher-student relationship in this context. Methodology: qualitative research, instrumental and multiple cases study method. Cases studied were public and private Universities. Results: the analysis produced six interrelated domains: being and practicing as a teacher in my university, a discussion about Higher Education reform and its implications on tutoring activities, the multiple meanings of tutoring, being and practicing as a student: the part ignored by the system, being and practicing as a tutor and, tutoring as a teaching and relationship space. The domain "being and practicing as a tutor" is presented in this paper as it is one of the most relevant issues of the study. Elements that impact on the meaning of being and practicing as a tutor are identified, as well as the roles, strategies and actions in the tutoring activities. Conclusions: "being a tutor" is influenced by the type of university, "being a teacher" and the sense of tutoring for teachers. Tutoring role is acquired, it can't be improvised. Teacher Training programs should be a powerful tools in order to change the meanings about teaching and to encourage attitudes towards tutoring action.